Αριθμητική προσομοιώση δισδιάστατου (2DH) κυματικού πεδίου με ύφαλη κατασκευή - Φλώρου, Εύη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών, 2014)
Low crested breakwaters have been widely used in the last few decades to protect coastal areas from erosion. Energy dissipation is achieved through wave-breaking and friction inside the structure. Their main advantage to conventional breakwaters is aesthetic. They also allow for circulation of water behind the structure so water quality does not decline. Wave transformation around permeable structures results in a very complicated wave field that cannot be predicted analytically nor empirically. In recent years mathematical models have been developed to model these effects. Boussinesq type models are more appropriate for modeling wave propagation in coastal areas. Typical Boussinesq equations are limited by weak non-linearity and dispersivity and are thus restricted to shallow water. To overcome this weakness many researchers have developed extended equations by retaining higher order terms. In this study we employ a non-linear, fully dispersive Boussinesq-type model (Chondros and Memos, 2014). The basic equations have been modified to account for flow inside a porous layer following the approach of Cruz et al. (1997). Model results are compared to data collected from the wave basin experiments in Aalborg University of Denmark during the DELOS project (DELOS, 2002).